IL-33 induces NF-κB activation in ILC2 that can be suppressed by in vivo and ex vivo 17β-estradiol - Trivedi, Shubhanshi; Labuz, Daniel; Deering-Rice, Cassandra E; Kim, Chu Un; Christensen, Hayden; Aamodt, Sam; Huecksteadt, Tom; Sanders, Karl; Warren, Kristi J. (Frontiers in Allergy, 2022)
Asthmatic women tend to develop severe airway disease in their reproductive years, and 30-40% of asthmatic women have peri-menstrual worsening of asthma symptoms. This indicates that fluctuations in ovarian hormones are involved in advancement of asthmatic disease and exacerbation of symptoms. Group 2 innate lymphoid cells, or ILC2, are readily detected in allergic conditions, such as rhinosinusitis, in individuals that develop nasal polyps do to allergen exposures, and in allergic asthma. ILC2 are airway localized immune cells activated by IL-33, an innate cytokine that perpetuates allergic inflammation by driving the production of IL-5 and IL-13. We have previously shown that ILC2 are highly activated in naïve and ovalbumin (OVA) challenged, female BALB/c mice in comparison to male mice following stimulation with IL-33. Here, we investigated the effect of steady-state ovarian hormones on ILC2 and the NF-κB signaling pathway following OVA sensitization and challenge. We found that estrogen-treated ovariectomized mice (OVX-E2) that had been challenged with OVA had reduced IL-5 and IL-13 production by lung ILC2 as compared to lung ILC2 isolated from intact male and female sham-operated controls that had been treated with OVA. ILC2 were isolated from untreated animals and co-cultured ex vivo with and without estrogen plus IL-33. Those estrogen-treated ILC2 similarly produced less IL-5 and IL-13 in comparison to untreated, and had reduced NF- κB activation. Single-cell RNA sequencing showed that 120 genes were differentially expressed in male and female ILC2, and Nfkb1 was found among top-ranked regulatory interactions. Together, these results provide new insight into the suppressive effect of estrogen on ILC2 which may be protective in female asthmatics. Understanding further how estrogen modulates ILC2 may provide therapeutic targets for the treatment of allergic diseases.